New Strait Times 28 January 2009 - Sager Ahmad (The New Straits Times Press (M) Bhd, 2009)
Contrary to popular belief, the Pacific War during World War 2 did not begin with the attack on Pearl Harbour, but on the beaches of Kota Baru.